Pengaruh Karakteristik Internal Auditor, Dukungan Manajemen Senior dan Budaya Organisasi Terhadap Efektivitas Internal Audit - Kusuma , Gumulya Sonny Marcel (Jurnal Keuangan dan Bisnis, 2021)
This study examines the influence of internal auditor, senior management support, organizational culture on the effectiveness of internal audits. This research uses convenience sampling technique to select the respondent . Data were collected through a survey on 44 respondents internal auditors who work at BUMN and BUMD of Palembang. Structural Equation Model (SEM) with Partial Least Square (PLS) was applied to analyzed the data. The result of this research indicate positive influence of internal auditor and senior management support on the effectiveness of internal audits. Futhermore, it was found that there were no significant influence organizational culture on the effectiveness of internal audits.